The Land Administration Domain Model. (December 2015) - Lemmen, Christiaan; van Oosterom, Peter; Bennett, Rohan
Abstract : Graphical abstract: The Core Classes of the Land Administration Domain Model. Highlights: The ISO 19152 Class Diagrams are presented UML. The impact of the Land Administration Domain Model is analysed. Abstract: Societal drivers including poverty eradication, gender equality, indigenous recognition, adequate housing, sustainable agriculture, food security, climate change response, and good governance, influence contemporary land administration design. Equally, the opportunities provided by technological development also influence design approaches. The Land Administration Domain Model (LADM) attempts to align both: the data model provides a standardised global vocabulary for land administration. As an international standard it can stimulate the development of software applications and may accelerate the implementation of land administration systems that support sustainability objectives. The LADM covers basic information-related components of land administration including those over land, in water, below the surface, and above the ground. The standard is an abstract, conceptual model with three packages related to: parties (people and organisations); basic administrative units, rights, responsibilities, and restrictions (ownership rights); spatial units (parcels, and the legal space of buildings and utility networks) with a sub package for surveying, and representation (geometry and topology). This paper examines the motivation, requirements and goals for developing LADM. Further, the standard itself is described and potential future maintenance. Despite being a very young standard, 'born' on 1st December 2012, it is already possible to observe some of the impact of LADM: examples are provided.